Sentuh Tanahku Application: As Land Conflict Mitigation An Impact on Sustainable Environmental in Papua Selatan - Yusuf, Andi Patta; Haning, Mohamad Thahir; Ibrahim, Muhammad Akmal; Hasniati, Hasniati; Adam, Aenal Fuad (Musamus Journal of Public Administration, 2024)
Papua Selatan occur land conflicts are a very important matter because they arise from unclear ownership of land and use of natural resources. Sentuh Tanahku Application is a digital innovation to enhance the transparency and access to information on ownership and use of land. The research examines the Utilization of this application in the mitigation of land conflict while considering their implications for sustainable environmental development. This is a qualitative method type of research with a literature study approach which emphasizes secondary data as sources that can be analyzed through the use of NVivo software. The results and findings indicated that the "Sentuh Tanahku" application was developed to minimize conflicts through the provision of transparent and accurate information about land boundaries. Digital maps, verification mechanisms for ownership rights, dispute reporting, and regulatory access are among other features provided by the app to promote transparency thus reducing uncertainty or ambiguity surrounding property rights which serve as roots for disputes. The “Sentuh Tanahku” Application can be used to report conflicts and actions taken on a factual basis thereby mitigating land disputes while also promoting environmental sustainability through the adoption of responsible and sustainable land use practices in Papua Selatan.